A penta-component mpox mRNA vaccine induces protective immunity in nonhuman primates - Qing Ye; Dong Zhang; Rong-Rong Zhang; Qian Xu; Xing-Yao Huang; Baoying Huang; Meng-Xu Sun; Zhe Cong; Lin Zhu; Jianrong Ma; Na Li; Jingjing Zhang; et al. (Nature Communications)
Abstract The recent worldwide outbreaks of mpox prioritize the development of a safe and effective mRNA vaccine. The contemporary mpox virus (MPXV) exhibits changing virological and epidemiological features, notably affecting populations already vulnerable to human immunodeficiency virus (HIV). Herein, we profile the immunogenicity of AR-MPXV5, a penta-component mRNA vaccine targeting five specific proteins (M1R, E8L, A29L, A35R, and B6R) from the representative contemporary MPXV clade II strain, in both naive and simian immunodeficiency virus (SIV)-infected nonhuman primates. Immunization with two doses of AR-MPXV5 to cynomolgus macaques effectively elicits antibody responses and cellular responses. Importantly, based on the challenge model with a contemporary MPXV clade II strain, AR-MPXV5 demonstrates effective efficacy in preventing skin lesions, eliminating viremia and reducing viral loads in multiple tissues after challenge in naive male animals. More importantly, AR-MPXV5 is well-tolerated in stable chronic SIV-infected rhesus monkeys, while eliciting comparable MPXV-specific humoral and cellular responses in both naive and SIV-infected monkeys. Together, these results support further clinical development of the AR-MPXV5 vaccine.